2021
DOI: 10.4103/ijnm.ijnm_112_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Effective Dose Received in Various Computed Tomography Protocols and Factors Affecting It

Abstract: Purpose of Study: The purpose of the study was to evaluate the effect of patient characteristics and equipment-related factors on the computed tomography (CT) dose received by patients from positron emission tomography-CT (PET-CT) using system-generated dose-length product (DLP) values and also to check the effective dose (ED) received from various CT protocols at our institute. Materials and Methods: This retrospective study included 78 adult patients who underwent F-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The study findings were also agreeable to the conclusion by 15 that variation in values reported by different CT scanners can vary between 10 and 15%. Dissimilar findings were reported by 16 who established that dose levels are not dependent on the equipment related factor of machine model. The difference in findings can be attributed to a number of institutional factors such radiology technicians given that the study was conducted in government referral hospital while the current study conducted among referral hospital and private hospitals.…”
Section: B Comparison Of the Ctdi(w) And Dlp Values For Adult Abdomin...mentioning
confidence: 52%
“…The study findings were also agreeable to the conclusion by 15 that variation in values reported by different CT scanners can vary between 10 and 15%. Dissimilar findings were reported by 16 who established that dose levels are not dependent on the equipment related factor of machine model. The difference in findings can be attributed to a number of institutional factors such radiology technicians given that the study was conducted in government referral hospital while the current study conducted among referral hospital and private hospitals.…”
Section: B Comparison Of the Ctdi(w) And Dlp Values For Adult Abdomin...mentioning
confidence: 52%
“…Rational selection of exposure condition and optimization of relation parameters can effectively reduce radiation dose in a PET/CT examination without affecting image quality. A previous report [22] found that patient ED mostly depends on scan range and tube current. Tonkopi, E. et al [23] proposed an approach that sped up X-ray tube rotation time, increasing X-ray beam coverage and noise index value to achieve radiation reduction in the CT component, up to 32% reduction with using optimized CT protocol.…”
Section: Discussionmentioning
confidence: 94%